MINAT MAHASISWA SENI MUSIK PRODI PENDIDIKKAN SENI PERTUNJUKKAN FKIP UNIVERSITAS TANJUNGPURA PONTIANAK TERHADAP MUSIK DANGDUT - Saddam Saddam; Imma Fretisari; Asfar Munir (Universitas Tanjungpura, 2019)
AbstractThe study based on the students ' lack of interest ofDangdut music and there wasa tendency that Music Students were more interested with Western music and popular music at this time.. The problem of this research was how music student interests against Dangdut music and why in any event shows held by Prodi and art students community rarely used instruments Dangdut?. This research was about Performance Art Education student interest in Tanjungpura University Pontianak Against Dangdut Music. The study was conducted at Performance Art Education FKIP UNTAN. Data obtained through this research was the description of the facts concerning the interest of students Towards Dangdut Music. The data were analyzed qualitatively with resource data that was Mr. H. M. Yaman Umar, and Music Student of Performance Art Education of UNTAN who know about the Dangdut Music. The data obtained through interviews, observation, documentation, and question form.Based on the data analysis can be concluded that; (1) the interest of Performance Art Education students towards Dangdut Music, where the average respondents who chose